Incertezas perante o georreferenciamento de imóveis rurais e a retificação extrajudicial - Borges Júnior, Carlos Roberto (2017)
The identification of the limits and the review of the domain of a land parcel is in an advanced stage of development in Brazil, primarily due to the consolidation of the georeferencing of rural properties and the Law of Public Records. However, due to the geospatial data reception computerization, through the Land Management System (Sistema de Gestão Fundiária - SIGEF) in 2013, there was a significant acceleration in the issue of certification by National Institute for Colonization and Agrarian Reform (Instituto Nacional de Colonização e Reforma Agrária – INCRA), not followed at same rate by Land Registry (Cartórios de Registro de Imóveis - CRI), in the case of administrative rectification caused by the change of the area and perimeter values inserted in the registered Legal Descriptions. In this sense, this work aims to presente the barriers that still affect the cadastre of land parcels and on the legal assessment of a parcel, proposing possibilities for implementation of the georeferencing of rural properties and de-bureaucracy at the administrative rectification. Therefore, it still the case today: the existence of the building at least three georeferenced database referring to the land parcels without the fusion of the information; the adoption of exacts values for area and perimeter, by both INCRA and the CRI, while should be considered as accurate and precise; and, multiple interpretations for the Law of Public Records, which converge into the slow conclusion of the administrative rectification. Thus, it was found the possibility to use different area values for the same land parcels between the Universal Transversa de Mercator (UTM) System and the Local Geodetic System (SGL), with a variation of ±0,15%, and the possibility to use mathematical discrepancy in the analysis of the limits of the land parcel, considering the limit of 1% between the area and perimeter values georeferenced and registered, for georeferenced points containing precisions to 50 centimeters, or the limit of 3% for georeferenced points containing precisions to 1,5 meter, or based on the use of the Mean Squared Error (Erro Médio Quadrático - EMQ). Moreover, it has been shown proposal for submission of technical report at the CRI, from the case studies on georeferenced land parcels, containing artificial or natural limits, suggesting the removal of administrative rectification or only of the authorization by neighbour properties, when mathematics and technically proven.